The Impression of Blood Droplets on Solid Surface and its Evaluation with Bloodstain Pattern Analysis, A Cross Section Forensic Study - Javed Iqbal Khokhar, Salman Pervaiz Rana, Tufail Ahmed Soomro, Sadaf Nadir, Muhammad Ikram Ali, Mohsana Urooj Rana (Pakistan Journal of Medical & Health Sciences, 2022)
Task: The aims and objectives of current study were to identify the values of bloodstain pattern analysis for blood droplets on solid surface in forensic sciences. Methodology: Study design: Present study was conducted in different medical institutions of Lahore from November 2021to March 2022. Crime scene (Blood droplets on solid surface): In current study for research purpose few blood droplets of 2 individuals were dropped on different solid surfaces and consider it as crime scene. Sample collection: In this study total 10 blood samples were collected from different individuals for cross match with the droplets of blood sample collected from solid surfaces. 2, individuals how dropped their blood droplets on solid surfaces were also included in total participants of present study. Blood droplets from solid surfaces were collected with the help of cotton swab techniques. DNA analysis: With the application of Polymerase chain reaction such analysis performed and DNA released from the cell by extraction and measured the amount of genetic material than amplified its copies and separated these amplified copies from each other. The qualitatively and quantitatively comparing of DNA evidence samples are referred as DNA profiles and checking the technical correctness of analyst reports was its quality assurance. Solution for blood stain identification: Luminol in the presence of H2O2 to combine with heme group of blood and created bright blue glow called chemiluminescence and with the help of such glow dried blood on surfaces can be detected. Bio-statistical analysis: Raw data bio-statistically represented by the application of SPSS model 2020, regression of different parameters showed as mean standard deviation of significant (P<0.05) changes. Results: DNA samples from blood droplets on solid surface (crime scene) and 10 other individuals (possible suspects) were processed. In present study for cross match analysis particular genetic marker i.e. two alleles or versions was considered which match the possible suspects DNA with the DNA from crime scene. The other has two copies of the repetition, whereas the first only has one (see the brown section below) the repetition is duplicated in the other, though whereas the second allele yields a 300 bp DNA fragment, the first allele yields a 200 bp DNA fragment. For 10, DNA samples perform PCR and Utilize gel electrophoresis technique for DNA matching. It has seen that two pair of alleles of sample A from crime scene DNA at 300bp (1.0±0.1 ) and 200 bp (1.2±0.4) have closed relation with the same DNA alleles of suspects-1 and two pair of alleles of sample B from crime scene DNA at 300bp (1.3±0.2) and 200 bp (1.5±0.1) showed resemblance with suspect-10 comparatively. The measured mean standard deviation levels of alleles similarities are significant (P<0.05) regarding standard measures. Conclusion: Blood is an important source of information that, when properly understood, may be utilized as a source of information to support investigations. Thus, a correlation between the development of blood stains and height was established. Keywords: Bloodstain pattern analyzers, crime scene, suspects, regression, blood droplets